TRP channels with diverse permeability profiles: regulation of blood pressure and fertility - Freichel, Marc (Henry Stewart Talks, 2014)
TRP channels: regulation of blood pressure and fertility, Transient receptor potential channels, regulation of intracellular Ca2+ homeostasis by cation channels with diverse permeability profiles, TRPM4 and catecholamine secretion from chromaffin cells, TRPV6-mediated Ca2+ uptake in epididymal epithelium, Ca2+ homeostasis in epididymal fluid and male fertility